A nickel disulfide / titanium dioxide / carbon composite material and its preparation method and application

By forming a porous spherical structure composed of nanoneedles in nickel disulfide/titanium dioxide/carbon composite materials, the volume expansion and low-magnification performance problems of nickel disulfide in potassium ion batteries are solved, and excellent cycle stability and high magnification are achieved. performance.

CN118978197BActive Publication Date: 2024-12-13SHENZHEN HONGZHUAN INTELLECTUAL PROPERTY MANAGEMENT SERVICE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411434175.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-13
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

Nickel disulfide is prone to volume expansion, loss of active material and low-ratio performance in potassium ion batteries, and the structure of the existing composite materials is not stable enough, resulting in poor cycle stability and rate performance.

Method used

Through the hydrothermal reaction of the nickel source, weak base and nano-titanium dioxide dispersion, Ni(OH)2/TiO2 composite material is formed, and reacted with dopamine hydrochloride and trimethylolamide to form Ni(OH)2/TiO2/dopamine The polymer composite material is then mixed with sulfur powder and heat-treated to obtain a NiS2/TiO2/carbon composite material, which has a porous spherical structure composed of nanoneedles, with nano nickel disulfide and nanotitanium dioxide sealed to nitrogen-doped carbon In the layer.

Benefits of technology

The composite material eases volume expansion during charging and discharging, improves cycle stability and rate performance, maintains a high reversible specific capacity, and improves conductivity and polar adsorption capacity through a nitrogen-doped carbon layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118978197B_ABST
    Figure CN118978197B_ABST
Patent Text Reader

Abstract

The invention discloses a nickel disulfide / titanium dioxide / carbon composite material and a preparation method and application thereof, and relates to the technical field of potassium ion batteries. The invention obtains a Ni(OH)2 / TiO2 composite material by mixing a nickel source, a weak base and a nano-TiO2 dispersion, and then reacting the mixture with dopamine hydrochloride and tris(hydroxymethylaminomethane) to obtain a Ni(OH)2 / TiO2 / dopamine polymer composite material, and then heat-treating the mixture with sulfur powder to obtain a nickel disulfide / titanium dioxide / carbon composite material. The nickel disulfide / titanium dioxide / carbon composite material presents a porous spherical structure composed of intersecting nanoneedles. The nanoneedles are composed of nickel disulfide nanoparticles with potassium intercalation activity and titanium dioxide nanoparticles with polar adsorption of potassium polysulfide sealed in a nitrogen atom-doped carbon layer. When used as a negative electrode material for a potassium ion battery, it exhibits good cycle stability and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of potassium ion batteries, and in particular to a nickel disulfide / titanium dioxide / carbon composite material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable appliances and electric vehicles due to their unique properties such as high voltage, low self-discharge rate, small size, light weight, and no memory effect. However, their energy density has been increasing slowly and their cost has been gradually rising, which has greatly restricted their further development. Potassium-ion batteries, as a new type of alternative energy storage battery, have a low price and rich potassium source, and are closest to the standard reduction potential of lithium-ion batteries, so they have high energy density. The high electrochemical activity of potassium-ion battery electrolyte is conducive to the transmission of ions and electrons. Therefore, potassium-ion batteries have become a powerful alternative to lithium-ion batteries.

[0003] Negative electrode materials play a vital role in the energy density, cycle life and rate performance of batteries. At present, the negative electrode materials that can be used as potassium ion batteries are mainly: carbon materials, transition metal oxides and transition sulfides. Among them, carbon materials have a low potassium deintercalation potential and are prone to form dendrites, causing safety hazards; transition metal oxides have defects such as particle size dependence, poor reversibility of large sizes, low energy efficiency, rapid capacity decay and poor rate performance. Transition metal sulfides benefit from the multi-electron electrochemical conversion reaction mechanism and have a high theoretical specific capacity.

[0004] Among transition metal sulfides, nickel disulfide has broad application prospects in the field of large-scale energy storage due to its high earth abundance, low cost, and environmental friendliness. Therefore, it has become one of the best candidates for negative electrode materials for potassium ion batteries. However, nickel disulfide is prone to volume expansion during the charging and discharging process, which leads to the crushing and shedding of active materials, resulting in the loss of active materials and a rapid decrease in capacity. At the same time, due to its low electronic conductivity, nickel disulfide undergoes severe polarization under high current charging and discharging conditions, and thus has problems such as low rate performance. In addition, nickel disulfide will produce potassium polysulfide intermediates in the process of potassium ion extraction and insertion. The potassium polysulfide is prone to shuttle effect in the electrolyte, causing rapid decay of potassium storage capacity. These problems have seriously hindered the continued application of nickel disulfide in the field of potassium ion batteries.

[0005] In the prior art, CN116137325A discloses a nickel disulfide / dual-phase titanium dioxide / carbon nanotube composite material and its preparation method and application. The titanium dioxide in the composite material acts as a buffer layer to slow down the volume expansion of nickel disulfide during lithium storage, and also has a certain chemical adsorption effect on the polysulfide generated during the charge and discharge process, thereby extending the life of the electrode. The external three-dimensional network constructed by the carbon nanotubes promotes the rapid transmission of electrons, and the large specific surface area provided is also conducive to the infiltration of the electrolyte and ion exchange. However, the prepared composite material presents a broken yolk shell structure, and the outer shell cannot protect the inner core well, so its electrochemical performance is poor.

[0006] Therefore, how to modify nickel disulfide to prepare nickel disulfide electrode materials, while improving its cycle stability and rate performance as a negative electrode material for potassium ion batteries, is an urgent problem to be solved. Summary of the invention

[0007] In view of the above-mentioned prior art, the purpose of the present invention is to provide a nickel disulfide / titanium dioxide / carbon composite material and its preparation method and application. The present invention obtains a Ni(OH)2 / TiO2 composite material by mixing a nickel source, a weak base and a nano-titanium dioxide dispersion, and then reacting the mixture with dopamine hydrochloride and tris(hydroxymethylaminomethane) to obtain a Ni(OH)2 / TiO2 / dopamine polymer composite material, and then mixing the mixture with sulfur powder and heat treating the mixture to obtain a NiS2 / TiO2 / carbon composite material. The NiS2 / TiO2 / carbon composite material presents a porous spherical structure composed of nano needles, and the nano needles are formed by nano nickel disulfide and nano titanium dioxide sealed in a nitrogen-doped carbon layer. Due to the unique porous structure of the composite, the superior conductivity of the nitrogen-doped carbon coating layer, the small size of the nano nickel disulfide itself, and the polar adsorption characteristics of nano titanium dioxide to potassium polysulfide, the composite material exhibits excellent potassium storage performance when used as a negative electrode material for potassium ion batteries.

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] A first aspect of the present invention provides a method for preparing a nickel disulfide / titanium dioxide / carbon composite material, comprising the following steps:

[0010] (1) mixing a nickel source and a weak base, adding the mixture to a nano-titanium dioxide dispersion, stirring to obtain a mixed solution, subjecting the mixed solution to a hydrothermal reaction, and after the reaction is completed, collecting the precipitate, washing, and drying to obtain a nickel hydroxide / titanium dioxide composite material;

[0011] (2) dispersing the nickel hydroxide / titanium dioxide composite material in deionized water to obtain a nickel hydroxide / titanium dioxide solution, mixing dopamine hydrochloride and tris(hydroxymethylaminomethane) and adding them to the nickel hydroxide / titanium dioxide solution, stirring to obtain a reaction product, filtering the reaction product, taking a precipitate, washing, and drying to obtain a nickel hydroxide / titanium dioxide / dopamine polymer composite material;

[0012] (3) The nickel hydroxide / titanium dioxide / dopamine polymer composite material and sulfur powder are mixed and placed in an inert atmosphere for heat treatment to obtain a nickel disulfide / titanium dioxide / carbon composite material.

[0013] Preferably, in step (1), the nano-titanium dioxide dispersion is prepared by mixing nano-titanium dioxide and deionized water in a solid-liquid ratio of (0.15-0.25) g:60 mL.

[0014] Preferably, in step (1), the nickel source is one of nickel nitrate hexahydrate, nickel chloride hexahydrate, and nickel sulfate hexahydrate.

[0015] Preferably, in step (1), the weak base is one of urea, ammonium carbonate, ammonium bicarbonate and sodium carbonate.

[0016] Preferably, in step (1), the ratio of the added amounts of the nickel source, the weak base and the nano-titanium dioxide in the nano-titanium dioxide dispersion is (0.5-2) mmol: (10-50) mmol: (0.15-0.25) g.

[0017] Preferably, in step (1), the hydrothermal reaction temperature is 80-200° C., and the hydrothermal reaction time is 10-18 h.

[0018] Preferably, in step (2), in the nickel hydroxide / titanium dioxide solution, the material-liquid ratio of the nickel hydroxide / titanium dioxide composite material to deionized water is 0.2 g:300 mL.

[0019] Preferably, in step (2), the addition ratio of dopamine hydrochloride, tris(hydroxymethylaminomethane) and the nickel hydroxide / titanium dioxide composite material in the nickel hydroxide / titanium dioxide solution is (0.5-1.5) mmol: (0.2-1) mmol: 0.2 g.

[0020] Preferably, in step (2), the stirring time is 10-14 hours.

[0021] Preferably, in step (3), the mass ratio of the nickel hydroxide / titanium dioxide / dopamine polymer composite material to the sulfur powder is 1:(1-10).

[0022] Preferably, in step (3), the inert atmosphere is an argon atmosphere.

[0023] Preferably, in step (3), the heat treatment operation is: heating to 400-800°C at a heating rate of 2-10°C / min, and keeping the temperature for 1-6h.

[0024] A second aspect of the present invention provides a nickel disulfide / titanium dioxide / carbon composite material.

[0025] Preferably, the nickel disulfide / titanium dioxide / carbon composite material is a porous spherical structure composed of nanoneedles, and the nanoneedles are formed by nano-nickel disulfide and nano-titanium dioxide sealed in a nitrogen atom-doped carbon layer.

[0026] Preferably, the particle size of the nano nickel disulfide is 20-50 nm, and the particle size of the nano titanium dioxide is 5-10 nm.

[0027] The third aspect of the present invention provides an application of a nickel disulfide / titanium dioxide / carbon composite material in the preparation of a negative electrode material for a potassium ion battery.

[0028] Preferably, the potassium ion battery negative electrode material is prepared by the following method: nickel disulfide / titanium dioxide / carbon composite material, acetylene black, and sodium carboxymethyl cellulose are mixed in a mass ratio of 8:1:1, added to deionized water, stirred evenly, coated on copper foil, and then placed in a vacuum dryer at 80°C for 12 hours to obtain a sodium ion battery negative electrode material.

[0029] More preferably, the copper foil has a thickness of 25 μm.

[0030] Beneficial effects of the present invention:

[0031] The present invention obtains a Ni(OH)2 / TiO2 composite material by mixing a nickel source, a weak base and a nano titanium dioxide dispersion liquid, and then reacting the mixture with dopamine hydrochloride and tris(hydroxymethyl)aminomethane to obtain a Ni(OH)2 / TiO2 / dopamine polymer composite material, and then heat-treating the mixture with sulfur powder to obtain a NiS2 / TiO2 / C composite material. The NiS2 / TiO2 / carbon composite material presents a porous spherical structure composed of nano needles, and the nano needles are formed by nano nickel disulfide and nano titanium dioxide sealed in a nitrogen-doped carbon layer.

[0032] The nickel disulfide / titanium dioxide / carbon composite material prepared by the present invention has a unique porous structure of the composite material, excellent conductivity of the nitrogen-doped carbon coating layer, small size of nano nickel disulfide itself and polar adsorption characteristics of nano titanium dioxide on potassium polysulfide. When used as a negative electrode material for a potassium ion battery, the composite material exhibits excellent potassium storage performance. When the charge and discharge current density is 0.1 A / g, the reversible specific capacity is maintained at 519.5 mAh / g after 100 cycles; when the charge and discharge current is increased to 5.0 A / g, the high reversible specific capacity of 361.1 mAh / g is still maintained. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 : Scanning electron microscopy image of the nickel hydroxide / titanium dioxide composite material prepared in Example 4;

[0034] Figure 2 : Scanning electron microscope image of the nickel disulfide / titanium dioxide / carbon composite material prepared in Example 4;

[0035] Figure 3 : XRD pattern of the nickel disulfide / titanium dioxide / carbon composite material prepared in Example 4;

[0036] Figure 4 : Electrochemical cycle life test diagram of the nickel disulfide / titanium dioxide / carbon composite material prepared in Example 4 and the materials prepared in Comparative Examples 1-3;

[0037] Figure 5 : Electrochemical rate performance test diagram of the nickel disulfide / titanium dioxide / carbon composite material prepared in Example 4 and the materials prepared in Comparative Examples 1-3. DETAILED DESCRIPTION

[0038] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0039] In the prior art, when nickel disulfide is used as the negative electrode material of potassium ion batteries, it is easy to expand in volume during the charge and discharge process, resulting in the crushing and falling off of active materials, etc., causing the loss of active materials and the rapid decrease of capacity. At the same time, due to its low electronic conductivity, nickel disulfide has serious polarization phenomenon under the condition of large current charge and discharge, and thus has problems such as low rate performance. In addition, nickel disulfide will produce potassium polysulfide intermediates in the process of extracting and embedding potassium ions. The potassium polysulfide is easy to shuttle in the electrolyte and cause the rapid decay of potassium storage capacity.

[0040] Although CN116137325A discloses a nickel disulfide / two-phase titanium dioxide / carbon nanotube composite material and its preparation method and application, the above patent Figure 1 and Figure 3 It can be seen that the structure of the composite material is a nickel disulfide / dual-phase titanium dioxide surface with a yolk-shell structure coated with a carbon nanotube conductive network. The composite material of this structure still has the following shortcomings: 1. Although the structure of the nickel / titanium dioxide / carbon composite β precursor presents an egg yolk-shell structure, many shells are in a broken state. It can be seen that the yolk-shell structure of the nickel disulfide / dual-phase titanium dioxide / carbon nanotube composite material obtained after the precursor is sulfurized also presents a large number of broken structures, and the outer shell cannot protect the inner core well; 2. Figure 3 It can be seen that since the carbon nanotube conductive network is coated on the surface of nickel disulfide / dual-phase titanium dioxide and presents a porous structure, and the yolk-shell structure of nickel disulfide / dual-phase titanium dioxide presents a large number of broken structures, the electrolyte will directly contact the core of nickel disulfide / dual-phase titanium dioxide and form a solid electrolyte membrane. Figure 1 It can be seen that the size of the nickel / titanium dioxide / carbon composite β precursor core is about 600nm, so it can be seen that the size of the nickel disulfide / dual-phase titanium dioxide core in the nickel disulfide / dual-phase titanium dioxide / carbon nanotube composite material is about 600nm. When lithium ions are inserted and removed, this large size will cause a large volume change, resulting in repeated formation and breakage of the solid electrolyte membrane, and then continuously consume the electrolyte to cause poor cycle stability. Since the potassium ion radius (1.38 Å) is much larger than the lithium ion radius (0.76 Å), it will show worse cycle stability when used as a negative electrode material for potassium ion batteries; 3. The larger size of the nickel disulfide / dual-phase titanium dioxide core will cause poor kinetics of lithium ion migration into it, showing poor rate performance. Combined with the above patent Table 1 and Figure 9, it can be seen that at a current density of 5 A / g, its reversible capacity is only 16.3% at a current density of 0.1 A / g. Since the radius of potassium ions is much larger than that of lithium ions, the migration kinetics of potassium ions in active materials are slower. Therefore, it can be seen that the composite material will exhibit worse rate performance when used as a negative electrode material for potassium ion batteries.

[0041] Based on this, the present invention provides a nickel disulfide / titanium dioxide / carbon composite material and its preparation method and application. The present invention obtains a Ni(OH)2 / TiO2 composite material by mixing a nickel source, a weak base and a nano-TiO2 dispersion liquid, and then reacting the mixture with dopamine hydrochloride and tris(hydroxymethyl)aminomethane to obtain a Ni(OH)2 / TiO2 / dopamine polymer composite material, and then mixing the mixture with sulfur powder and heat treating the mixture to obtain a NiS2 / TiO2 / carbon composite material. The NiS2 / TiO2 / carbon composite material presents a porous spherical structure composed of nano-needles, and the nano-needles are formed by nano-nickel disulfide and nano-titanium dioxide sealed in a carbon layer.

[0042] From the perspective of components, in the nickel disulfide / titanium dioxide / carbon composite material prepared by the present invention, the nickel disulfide sealed in the carbon layer is used as a potassium storage ion active material. Because its particle size is only 20-50nm, it not only shortens the diffusion path of potassium ions, but also can alleviate the volume expansion during the charge and discharge process by itself, and is also conducive to improving the cycle stability and rate performance of the composite material. The nano-titanium dioxide sealed in the carbon layer has a polar adsorption effect, which can polarly adsorb potassium polysulfide generated by nickel disulfide during the de- / insertion of potassium, prevent the occurrence of potassium polysulfide shuttle effect in the electrolyte, thereby improving the cycle stability performance when used as a negative electrode material for potassium ion batteries. The doping of nitrogen atoms is conducive to improving the conductivity of carbon.

[0043] The nitrogen-doped carbon coating layer obtained by heat treatment with dopamine in the present invention can not only greatly inhibit the mutual contact between nickel disulfide particles, thereby avoiding serious sintering into large particles due to contact, but also change the electronic structure of the carbon material by the incorporation of nitrogen atoms, increase the number of free electrons, and thus improve the conductivity of the composite material. Compared with pure carbon, nitrogen atom-doped carbon has better conductivity.

[0044] From a structural point of view, the nickel disulfide / titanium dioxide / carbon composite material prepared by the present invention presents a porous spherical structure composed of intersecting nanoneedles. On the one hand, the porous structure provides sufficient space for the volume change of nickel disulfide when it is deintercalating / intercalating potassium. On the other hand, it is also conducive to the flow of electrolyte in the composite material, increasing the contact between the nickel disulfide active material and the electrolyte, thereby shortening the diffusion distance of potassium ions, thereby simultaneously improving the cycle performance and rate performance when used as a negative electrode material for potassium ion batteries. The porous spherical structure formed by the intersecting nanoneedle structure has more porosity to alleviate the volume expansion effect of the nickel disulfide / titanium dioxide / carbon composite material when it is deintercalating and intercalating potassium ions, thereby improving its cycle stability, and a larger specific surface area to increase the contact between the nickel disulfide / titanium dioxide / carbon composite material and the electrolyte, thereby shortening the transmission distance of ions / electrons, thereby improving its rate performance.

[0045] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0046] The experimental materials used in the embodiments of the present invention are all conventional experimental materials in the art and can be purchased through commercial channels.

[0047] Example 1: Preparation of nickel disulfide / titanium dioxide / carbon composite material

[0048] (1) Nano-titanium dioxide and deionized water are mixed at a ratio of 0.2 g:60 mL, and then dispersed by ultrasonication to obtain a nano-titanium dioxide dispersion. Nickel nitrate hexahydrate and urea are mixed and added to the nano-titanium dioxide dispersion, and stirred until the nickel nitrate hexahydrate and the urea are completely dissolved to obtain a mixed solution, wherein the ratio of the added amount of nano-titanium dioxide in the nickel nitrate hexahydrate, urea and nano-titanium dioxide dispersion is 1 mmol:20 mmol:0.2 g. The mixed solution is placed at 100° C. for 10 hours. After the reaction is completed, the precipitate is collected, washed and dried to obtain a nickel hydroxide / titanium dioxide composite material;

[0049] (2) Mixing the nickel hydroxide / titanium dioxide composite material and deionized water at a ratio of 0.2 g:300 mL to obtain a nickel hydroxide / titanium dioxide solution, mixing dopamine hydrochloride and tris(hydroxymethylaminomethane) and adding them to the nickel hydroxide / titanium dioxide solution, stirring at room temperature for 12 h to obtain a reaction product, wherein the addition ratio of dopamine hydrochloride, tris(hydroxymethylaminomethane) and the nickel hydroxide / titanium dioxide composite material in the nickel hydroxide / titanium dioxide solution is 1 mmol:0.5 mmol:0.2 g, filtering the reaction product, taking the precipitate, washing and drying it, to obtain a nickel hydroxide / titanium dioxide / dopamine polymer composite material;

[0050] (3) The nickel hydroxide / titanium dioxide / dopamine polymer composite material and sulfur powder were mixed in a mass ratio of 1:5, placed in an argon atmosphere, heated to 500°C at a heating rate of 6°C / min, and kept warm for 2 h to obtain a nickel disulfide / titanium dioxide / carbon composite material.

[0051] Example 2: Preparation of nickel disulfide / titanium dioxide / carbon composite material

[0052] (1) Nano-titanium dioxide and deionized water are mixed at a ratio of 0.2 g:60 mL, and then dispersed by ultrasonication to obtain a nano-titanium dioxide dispersion. Nickel nitrate hexahydrate and urea are mixed and added to the nano-titanium dioxide dispersion, and stirred until the nickel nitrate hexahydrate and the urea are completely dissolved to obtain a mixed solution, wherein the ratio of the added amounts of nickel nitrate hexahydrate, urea and nano-titanium dioxide in the nano-titanium dioxide dispersion is 2 mmol:30 mmol:0.2 g. The mixed solution is placed at 120° C. for reaction for 12 hours. After the reaction is completed, the precipitate is collected, washed and dried to obtain a nickel hydroxide / titanium dioxide composite material;

[0053] (2) Mixing the nickel hydroxide / titanium dioxide composite material and deionized water at a ratio of 0.2 g:300 mL to obtain a nickel hydroxide / titanium dioxide solution, mixing dopamine hydrochloride and tris(hydroxymethylaminomethane) and adding them to the nickel hydroxide / titanium dioxide solution, stirring at room temperature for 12 h to obtain a reaction product, wherein the addition ratio of dopamine hydrochloride, tris(hydroxymethylaminomethane) and the nickel hydroxide / titanium dioxide composite material in the nickel hydroxide / titanium dioxide solution is 1.5 mmol:1 mmol:0.2 g, filtering the reaction product, taking the precipitate, washing and drying it, to obtain a nickel hydroxide / titanium dioxide / dopamine polymer composite material;

[0054] (3) The nickel hydroxide / titanium dioxide / dopamine polymer composite material and sulfur powder were mixed in a mass ratio of 1:5, placed in an argon atmosphere, heated to 500°C at a heating rate of 6°C / min, and kept warm for 2 h to obtain a nickel disulfide / titanium dioxide / carbon composite material.

[0055] Example 3: Preparation of nickel disulfide / titanium dioxide / carbon composite material

[0056] (1) Nano-titanium dioxide and deionized water are mixed at a ratio of 0.2 g:60 mL, and then dispersed by ultrasonication to obtain a nano-titanium dioxide dispersion. Nickel chloride hexahydrate and ammonium bicarbonate are mixed and added to the nano-titanium dioxide dispersion, and stirred until the nickel chloride hexahydrate and the ammonium bicarbonate are completely dissolved to obtain a mixed solution, wherein the ratio of the added amounts of nickel chloride hexahydrate, ammonium bicarbonate and nano-titanium dioxide in the nano-titanium dioxide dispersion is 1 mmol:20 mmol:0.2 g. The mixed solution is placed at 150° C. for reaction for 18 h. After the reaction is completed, the precipitate is collected, washed and dried to obtain a nickel hydroxide / titanium dioxide composite material;

[0057] (2) Mixing the nickel hydroxide / titanium dioxide composite material and deionized water at a ratio of 0.2 g:300 mL to obtain a nickel hydroxide / titanium dioxide solution, mixing dopamine hydrochloride and tris(hydroxymethylaminomethane) and adding them to the nickel hydroxide / titanium dioxide solution, stirring at room temperature for 12 h to obtain a reaction product, wherein the addition ratio of dopamine hydrochloride, tris(hydroxymethylaminomethane) and the nickel hydroxide / titanium dioxide composite material in the nickel hydroxide / titanium dioxide solution is 0.5 mmol:0.2 mmol:0.2 g, filtering the reaction product, taking the precipitate, washing and drying it, to obtain a nickel hydroxide / titanium dioxide / dopamine polymer composite material;

[0058] (3) The nickel hydroxide / titanium dioxide / dopamine polymer composite material and sulfur powder were mixed in a mass ratio of 1:4, placed in an argon atmosphere, heated to 600°C at a heating rate of 5°C / min, and kept warm for 3 hours to obtain a nickel disulfide / titanium dioxide / carbon composite material.

[0059] Example 4: Preparation of nickel disulfide / titanium dioxide / carbon composite material

[0060] (1) Nano-titanium dioxide and deionized water are mixed at a ratio of 0.2 g:60 mL, and then dispersed by ultrasonication to obtain a nano-titanium dioxide dispersion. Nickel chloride hexahydrate and urea are mixed and added to the nano-titanium dioxide dispersion, and stirred until the nickel chloride hexahydrate and the urea are completely dissolved to obtain a mixed solution, wherein the ratio of the added amounts of nickel chloride hexahydrate, urea and nano-titanium dioxide in the nano-titanium dioxide dispersion is 0.5 mmol:10 mmol:0.2 g. The mixed solution is placed at 160° C. for reaction for 18 h. After the reaction is completed, the precipitate is collected, washed and dried to obtain a nickel hydroxide / titanium dioxide composite material;

[0061] (2) Mixing the nickel hydroxide / titanium dioxide composite material and deionized water at a ratio of 0.2 g:300 mL to obtain a nickel hydroxide / titanium dioxide solution, mixing dopamine hydrochloride and tris(hydroxymethylaminomethane) and adding them to the nickel hydroxide / titanium dioxide solution, stirring at room temperature for 12 h to obtain a reaction product, wherein the addition ratio of dopamine hydrochloride, tris(hydroxymethylaminomethane) and the nickel hydroxide / titanium dioxide composite material in the nickel hydroxide / titanium dioxide solution is 0.8 mmol:0.8 mmol:0.2 g, filtering the reaction product, taking the precipitate, washing and drying it, to obtain a nickel hydroxide / titanium dioxide / dopamine polymer composite material;

[0062] (3) The nickel hydroxide / titanium dioxide / dopamine polymer composite material and sulfur powder were mixed in a mass ratio of 1:3, placed in an argon atmosphere, heated to 550°C at a heating rate of 10°C / min, and kept warm for 4 hours to obtain a nickel disulfide / titanium dioxide / carbon composite material.

[0063] Example 5: Preparation of nickel disulfide / titanium dioxide / carbon composite material

[0064] (1) Nano-titanium dioxide and deionized water are mixed at a ratio of 0.2 g:60 mL, and then dispersed by ultrasonication to obtain a nano-titanium dioxide dispersion. Nickel nitrate hexahydrate and ammonium bicarbonate are mixed and added to the nano-titanium dioxide dispersion, and stirred until the nickel nitrate hexahydrate and the ammonium bicarbonate are completely dissolved to obtain a mixed solution, wherein the ratio of the added amounts of nickel nitrate hexahydrate, ammonium bicarbonate and nano-titanium dioxide in the nano-titanium dioxide dispersion is 1.5 mmol:30 mmol:0.2 g. The mixed solution is placed at 80° C. for reaction for 16 h. After the reaction is completed, the precipitate is collected, washed and dried to obtain a nickel hydroxide / titanium dioxide composite material;

[0065] (2) Mixing the nickel hydroxide / titanium dioxide composite material and deionized water at a ratio of 0.2 g:300 mL to obtain a nickel hydroxide / titanium dioxide solution, mixing dopamine hydrochloride and tris(hydroxymethylaminomethane) and adding them to the nickel hydroxide / titanium dioxide solution, stirring at room temperature for 12 h to obtain a reaction product, wherein the addition ratio of dopamine hydrochloride, tris(hydroxymethylaminomethane) and the nickel hydroxide / titanium dioxide composite material in the nickel hydroxide / titanium dioxide solution is 1.5 mmol:1 mmol:0.2 g, filtering the reaction product, taking the precipitate, washing and drying it, to obtain a nickel hydroxide / titanium dioxide / dopamine polymer composite material;

[0066] (3) The nickel hydroxide / titanium dioxide / dopamine polymer composite material and sulfur powder were mixed in a mass ratio of 1:5, placed in an argon atmosphere, heated to 550°C at a heating rate of 10°C / min, and kept warm for 3 hours to obtain a nickel disulfide / titanium dioxide / carbon composite material.

[0067] Example 6: Preparation of nickel disulfide / titanium dioxide / carbon composite material

[0068] (1) Nano-titanium dioxide and deionized water are mixed at a ratio of 0.2 g:60 mL, and then dispersed by ultrasonication to obtain a nano-titanium dioxide dispersion. Nickel nitrate hexahydrate and urea are mixed and added to the nano-titanium dioxide dispersion, and stirred until the nickel nitrate hexahydrate and the urea are completely dissolved to obtain a mixed solution, wherein the ratio of the added amounts of nickel nitrate hexahydrate, urea and nano-titanium dioxide in the nano-titanium dioxide dispersion is 1 mmol:50 mmol:0.2 g. The mixed solution is placed at 100° C. for reaction for 12 h. After the reaction is completed, the precipitate is collected, washed and dried to obtain a nickel hydroxide / titanium dioxide composite material;

[0069] (2) Mixing the nickel hydroxide / titanium dioxide composite material and deionized water at a ratio of 0.2 g:300 mL to obtain a nickel hydroxide / titanium dioxide solution, mixing dopamine hydrochloride and tris(hydroxymethylaminomethane) and adding them to the nickel hydroxide / titanium dioxide solution, stirring at room temperature for 12 h to obtain a reaction product, wherein the addition ratio of dopamine hydrochloride, tris(hydroxymethylaminomethane) and the nickel hydroxide / titanium dioxide composite material in the nickel hydroxide / titanium dioxide solution is 1 mmol:0.5 mmol:0.2 g, filtering the reaction product, taking the precipitate, washing and drying it, to obtain a nickel hydroxide / titanium dioxide / dopamine polymer composite material;

[0070] (3) The nickel hydroxide / titanium dioxide / dopamine polymer composite material and sulfur powder were mixed in a mass ratio of 1:10, placed in an argon atmosphere, heated to 700°C at a heating rate of 8°C / min, and kept warm for 2 h to obtain a nickel disulfide / titanium dioxide / carbon composite material.

[0071] Example 7: Preparation of nickel disulfide / titanium dioxide / carbon composite material

[0072] (1) Nano-titanium dioxide and deionized water are mixed at a ratio of 0.15 g:60 mL, and then dispersed by ultrasonication to obtain a nano-titanium dioxide dispersion. Nickel nitrate hexahydrate and urea are mixed and added to the nano-titanium dioxide dispersion, and stirred until the nickel nitrate hexahydrate and the urea are completely dissolved to obtain a mixed solution, wherein the ratio of the added amounts of nickel nitrate hexahydrate, urea and nano-titanium dioxide in the nano-titanium dioxide dispersion is 0.5 mmol:10 mmol:0.15 g. The mixed solution is placed at 80° C. for reaction for 18 hours. After the reaction is completed, the precipitate is collected, washed and dried to obtain a nickel hydroxide / titanium dioxide composite material;

[0073] (2) Mixing the nickel hydroxide / titanium dioxide composite material and deionized water at a ratio of 0.2 g:300 mL to obtain a nickel hydroxide / titanium dioxide solution, mixing dopamine hydrochloride and tris(hydroxymethylaminomethane) and adding them to the nickel hydroxide / titanium dioxide solution, stirring at room temperature for 12 h to obtain a reaction product, wherein the added amount ratio of dopamine hydrochloride, tris(hydroxymethylaminomethane) and nickel hydroxide / titanium dioxide in the nickel hydroxide / titanium dioxide solution is 0.5 mmol:0.2 mmol:0.2 g, filtering the reaction product, taking the precipitate, washing and drying it, to obtain a nickel hydroxide / titanium dioxide / dopamine polymer composite material;

[0074] (3) The nickel hydroxide / titanium dioxide / dopamine polymer composite material and sulfur powder were mixed in a mass ratio of 1:1, placed in an argon atmosphere, heated to 400°C at a heating rate of 2°C / min, and kept warm for 1 hour to obtain a nickel disulfide / titanium dioxide / carbon composite material.

[0075] Example 8: Preparation of nickel disulfide / titanium dioxide / carbon composite material

[0076] (1) Nano-titanium dioxide and deionized water are mixed at a ratio of 0.25 g:60 mL, and then dispersed by ultrasonication to obtain a nano-titanium dioxide dispersion. Nickel nitrate hexahydrate and urea are mixed and added to the nano-titanium dioxide dispersion, and stirred until the nickel nitrate hexahydrate and the urea are completely dissolved to obtain a mixed solution, wherein the ratio of the added amounts of nickel nitrate hexahydrate, urea and nano-titanium dioxide in the nano-titanium dioxide dispersion is 2 mmol:50 mmol:0.25 g. The mixed solution is placed at 80° C. for reaction for 10 hours. After the reaction is completed, the precipitate is collected, washed and dried to obtain a nickel hydroxide / titanium dioxide composite material;

[0077] (2) Mixing the nickel hydroxide / titanium dioxide composite material and deionized water at a ratio of 0.2 g:300 mL to obtain a nickel hydroxide / titanium dioxide solution, mixing dopamine hydrochloride and tris(hydroxymethylaminomethane) and adding them to the nickel hydroxide / titanium dioxide solution, stirring at room temperature for 12 h to obtain a reaction product, wherein the addition ratio of dopamine hydrochloride, tris(hydroxymethylaminomethane) and the nickel hydroxide / titanium dioxide composite material in the nickel hydroxide / titanium dioxide solution is 1.5 mmol:1 mmol:0.2 g, filtering the reaction product, taking the precipitate, washing and drying it, to obtain a nickel hydroxide / titanium dioxide / dopamine polymer composite material;

[0078] (3) The nickel hydroxide / titanium dioxide / dopamine polymer composite material and sulfur powder were mixed in a mass ratio of 1:10, placed in an argon atmosphere, heated to 400°C at a heating rate of 10°C / min, and kept warm for 6 hours to obtain a nickel disulfide / titanium dioxide / carbon composite material.

[0079] Comparative Example 1:

[0080] (1) Mix nickel chloride hexahydrate and urea and add them to deionized water, stirring until the nickel chloride hexahydrate and urea are completely dissolved to obtain a mixed solution, wherein the ratio of the added amounts of nickel chloride hexahydrate, urea and deionized water is 0.5 mmol:10 mmol:60 mL, and the mixed solution is placed at 160° C. for 18 hours. After the reaction is completed, the precipitate is collected, washed and dried to obtain a nickel hydroxide material;

[0081] (2) Mix nickel hydroxide material and sulfur powder in a mass ratio of 1:3, place in an argon atmosphere, heat to 550°C at a heating rate of 10°C / min, and keep warm for 4 hours to obtain nickel disulfide material.

[0082] Comparative Example 2:

[0083] (1) Nano-titanium dioxide and deionized water are mixed at a ratio of 0.2 g:60 mL, and then dispersed by ultrasonication to obtain a nano-titanium dioxide dispersion. Nickel chloride hexahydrate and urea are mixed and added to the nano-titanium dioxide dispersion, and stirred until the nickel chloride hexahydrate and the urea are completely dissolved to obtain a mixed solution, wherein the ratio of the added amount of nano-titanium dioxide in the nickel chloride hexahydrate, urea and nano-titanium dioxide dispersion is 0.5 mmol:10 mmol:0.2 g. The mixed solution is placed at 160° C. for 18 hours. After the reaction is completed, the precipitate is collected, washed and dried to obtain a nickel hydroxide / titanium dioxide composite material;

[0084] (2) The nickel hydroxide / titanium dioxide composite material and sulfur powder were mixed in a mass ratio of 1:3, placed in an argon atmosphere, heated to 550°C at a heating rate of 10°C / min, and kept warm for 4 hours to obtain a nickel disulfide / titanium dioxide composite material.

[0085] Comparative Example 3:

[0086] (1) Mix nickel chloride hexahydrate and urea and add them to deionized water, stirring until the nickel chloride hexahydrate and urea are completely dissolved to obtain a mixed solution, wherein the ratio of the added amounts of nickel chloride hexahydrate, urea and deionized water is 0.5 mmol:10 mmol:60 mL, and the mixed solution is placed at 160° C. for 18 hours. After the reaction is completed, the precipitate is collected, washed and dried to obtain a nickel hydroxide material;

[0087] (2) Mixing nickel hydroxide material and deionized water at a ratio of 0.2 g:300 mL to obtain a nickel hydroxide solution, mixing dopamine hydrochloride and tris(hydroxymethylaminomethane) and adding them to the nickel hydroxide solution, stirring at room temperature for 12 hours to obtain a reaction product, wherein the added amount ratio of dopamine hydrochloride, tris(hydroxymethylaminomethane) and the nickel hydroxide material in the nickel hydroxide solution is 0.8 mmol:0.8 mmol:0.2 g, filtering the reaction product, taking the precipitate, washing and drying it, and obtaining a nickel hydroxide / dopamine polymer composite material;

[0088] (3) The nickel hydroxide / dopamine polymer composite material and sulfur powder were mixed in a mass ratio of 1:3, placed in an argon atmosphere, heated to 550°C at a heating rate of 10°C / min, and kept warm for 4 hours to obtain a nickel disulfide / carbon composite material.

[0089] Test Example 1: Structural Characterization

[0090] The nickel disulfide / titanium dioxide / carbon composite material prepared in Example 4 was characterized by the following structure: Figure 1-Figure 3 shown.

[0091] Depend on Figure 1It can be seen that the nickel hydroxide / titanium dioxide composite material prepared by the present invention has a spherical structure composed of nanoneedles. The formation of the nanoneedles is due to the hydrolysis of urea under hydrothermal conditions to generate urate ions, and the H + Combined with urate ions to form uric acid, the remaining OH - It is adsorbed on the surface of nano-titanium dioxide and combined with nickel ions to form nickel hydroxide, which then coats the nano-titanium dioxide and grows into nano-needles, which then cross each other to form a sphere. The structure formed in this step provides the basis for the later formation of nano-nickel disulfide and nano-titanium dioxide sealed in the carbon layer.

[0092] Depend on Figure 2 It can be seen that the nickel disulfide / titanium dioxide / carbon composite material prepared by the present invention presents a porous spherical structure, and the porous sphere is composed of carbon-coated nano nickel disulfide and titanium dioxide nanoneedles. The porous structure is beneficial to increase the contact area between the nickel disulfide / titanium dioxide / carbon composite material and the electrolyte when used as an electrode material. At the same time, it can also provide an effective space for the volume change of nickel disulfide during the de- / embedding of potassium ions, thereby improving the cycle stability of the electrode material. The formation of the carbon layer is obtained by carbonization of polydopamine, and the dopamine monomer contains nitrogen elements. Therefore, the carbon layer is carbon doped with nitrogen atoms. After nitrogen atoms doping carbon, the conductivity of carbon can be greatly improved, which is beneficial to the rate performance of the nickel disulfide / titanium dioxide / carbon composite material as the negative electrode of potassium ion batteries. In addition, from Figure 2 It can also be seen that the nanoparticles sealed in the carbon layer are very small, indicating that the particle size of the nano nickel disulfide obtained by sulfidation of nickel hydroxide is very small. This is because the presence of the carbon layer greatly inhibits the mutual contact between the nickel disulfide particles, thereby avoiding the serious sintering into large particles caused by contact. Nickel disulfide is used as an active substance for potassium storage in nickel disulfide / titanium dioxide / carbon composite materials. The small particle size of nickel disulfide, on the one hand, alleviates its own volume change caused by the removal / embedding of potassium ions, and on the other hand, it can also shorten the diffusion path of electrons / potassium ions, thereby improving the electrochemical cycle stability and rate performance of nickel disulfide / titanium dioxide / carbon composite materials to a certain extent. Titanium dioxide plays a major role in polar adsorption of potassium polysulfide in the composite material, preventing the loss of potassium polysulfide formed by nickel disulfide during charging and discharging, which is beneficial to the electrochemical cycle stability of nickel disulfide / titanium dioxide / carbon composite materials.

[0093] Depend on Figure 3 It can be seen that the XRD spectrum of the nickel disulfide / titanium dioxide / carbon composite material prepared in the present invention is consistent with the standard PDF card of nickel disulfide (JCPDF NO.11-0099) and the standard PDF card of titanium dioxide (JCPDF NO.21-1272), respectively, proving that the composite material is composed of nickel disulfide and titanium dioxide.

[0094] Test Example 2:

[0095] The nickel disulfide / titanium dioxide / carbon composite material prepared in Example 4 and the materials prepared in Comparative Examples 1-3 were used to prepare negative electrode materials and assembled into potassium ion batteries. The electrochemical cycle stability and rate performance of the batteries were tested. The results are as follows: Figure 4-Figure 5 shown.

[0096] Among them, the charge and discharge current density of the cycle stability performance test is 0.1 A / g, and the cut-off charge and discharge voltage is 0.1-3 V; the charge and discharge current density of the rate performance test is 0.1, 0.2, 0.5, 1.0, 2.0, and 5.0 A / g, respectively, and the cut-off charge and discharge voltage is 0.1-3V.

[0097] The preparation method of the negative electrode material is as follows: nickel disulfide / titanium dioxide / carbon composite material, acetylene black, and sodium carboxymethyl cellulose are added to deionized water at a mass ratio of 8:1:1, stirred evenly, and then coated on a 25μm thick copper foil, and then placed in a vacuum drying oven at 80°C for 12 hours and taken out, and the copper foil is cut into a 16mm diameter disc with a cutting machine to form a negative electrode. The negative electrode is directly assembled with potassium metal as a counter electrode into a button cell to measure its electrochemical performance, wherein the electrolyte is 0.8M KPF6 / DEC:EC (1:1, volume ratio).

[0098] Depend on Figure 4 It can be seen that when the nickel disulfide / titanium dioxide / carbon composite material prepared by the present invention is used as a potassium ion negative electrode material, the reversible specific capacity is maintained at 519.5 mAh / g after 100 cycles under the test current of 0.1 A / g. The material prepared in comparative example 1 is used as a potassium ion battery negative electrode material. After 100 cycles under the test current of 0.1 A / g, the reversible specific capacity can only be maintained at 68.8 mAh / g. The material prepared in comparative example 2 is used as a potassium ion battery negative electrode material. After 100 cycles under the test current of 0.1 A / g, the reversible specific capacity is maintained at 224.4 mAh / g. The material prepared in comparative example 3 is used as a potassium ion battery negative electrode material. After 100 cycles under the test current of 0.1 A / g, the reversible specific capacity is maintained at 145.0 mAh / g. It can be seen that the structural stability of the composite material of the present invention and the superiority of the polar adsorption of potassium polysulfide by titanium dioxide.

[0099] Depend on Figure 5It can be seen that in terms of rate performance, the nickel disulfide / titanium dioxide / carbon composite material prepared by the present invention can still be maintained at 361.1 mAh / g as a potassium ion negative electrode material under a current density of 5.0 A / g test, the material prepared in comparative example 1 as a potassium ion negative electrode material is only maintained at 4.2 mAh / g under a current density of 5.0 A / g test, the material prepared in comparative example 2 as a potassium ion negative electrode material is only maintained at 131.9 mAh / g under a current density of 5.0 A / g test, and the material prepared in comparative example 3 as a potassium ion negative electrode material is only maintained at 52.3 mAh / g under a current density of 5.0 A / g test. It can be seen that the small particle size of nickel disulfide, the improved conductivity of nitrogen atom-doped carbon, and the porous structure increase The contact area between the composite material and the electrolyte causes the shortened diffusion path of potassium ions, and the three combine to jointly improve the overall rate performance of the composite material.

[0100] Therefore, the present invention provides a method for preparing a nickel disulfide / titanium dioxide / carbon composite material. The prepared nickel disulfide / titanium dioxide / carbon composite material has excellent cycle stability and rate performance as a negative electrode material for potassium ion batteries.

[0101] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a nickel disulfide / titanium dioxide / carbon composite material, characterized in that: The following steps are involved: (1) mixing a nickel source and a weak base, adding the mixture to a nano-titanium dioxide dispersion, stirring to obtain a mixed solution, subjecting the mixed solution to a hydrothermal reaction, and after the reaction is completed, collecting the precipitate, washing, and drying to obtain a nickel hydroxide / titanium dioxide composite material, wherein the weak base is one of urea, ammonium carbonate, ammonium bicarbonate, and sodium carbonate; (2) dispersing the nickel hydroxide / titanium dioxide composite material in deionized water to obtain a nickel hydroxide / titanium dioxide solution, mixing dopamine hydrochloride and tris(hydroxymethylaminomethane) and adding them to the nickel hydroxide / titanium dioxide solution, stirring to obtain a reaction product, filtering the reaction product, taking a precipitate, washing, and drying to obtain a nickel hydroxide / titanium dioxide / dopamine polymer composite material; (3) mixing the nickel hydroxide / titanium dioxide / dopamine polymer composite material and sulfur powder, and placing the mixture in an inert atmosphere for heat treatment to obtain a nickel disulfide / titanium dioxide / carbon composite material; The nickel disulfide / titanium dioxide / carbon composite material presents a porous spherical structure composed of nano needles, and the nano needles are formed by nano nickel disulfide and nano titanium dioxide sealed in a nitrogen-doped carbon layer.

2. The method for preparing the nickel disulfide / titanium dioxide / carbon composite material according to claim 1, characterized in that: In step (1), the nano-titanium dioxide dispersion is prepared by mixing nano-titanium dioxide and deionized water in a solid-liquid ratio of (0.15-0.25) g:60 mL.

3. The method for preparing the nickel disulfide / titanium dioxide / carbon composite material according to claim 1, characterized in that: In step (1), the nickel source is one of nickel nitrate hexahydrate, nickel chloride hexahydrate, and nickel sulfate hexahydrate.

4. The method for preparing the nickel disulfide / titanium dioxide / carbon composite material according to claim 1, characterized in that: The added amount ratio of the nickel source, the weak base and the nano-titanium dioxide in the nano-titanium dioxide dispersion is (0.5-2) mmol: (10-50) mmol: (0.15-0.25) g, the hydrothermal reaction temperature is 80-200° C., and the hydrothermal reaction time is 10-18 hours.

5. The method for preparing the nickel disulfide / titanium dioxide / carbon composite material according to claim 1, characterized in that: In step (2), in the nickel hydroxide / titanium dioxide solution, the material-liquid ratio of the nickel hydroxide / titanium dioxide composite material to deionized water is 0.2 g:300 mL.

6. The method for preparing the nickel disulfide / titanium dioxide / carbon composite material according to claim 1, characterized in that: In step (2), the added amount ratio of dopamine hydrochloride, tris(hydroxymethylaminomethane) and the nickel hydroxide / titanium dioxide composite material in the nickel hydroxide / titanium dioxide solution is (0.5-1.5) mmol: (0.2-1) mmol: 0.2 g.

7. The method for preparing the nickel disulfide / titanium dioxide / carbon composite material according to claim 1, characterized in that: In step (3), the mass ratio of the nickel hydroxide / titanium dioxide / dopamine polymer composite material to the sulfur powder is 1:(1-10).

8. The method for preparing the nickel disulfide / titanium dioxide / carbon composite material according to claim 1, characterized in that: The inert atmosphere in step (3) is an argon atmosphere, and the heat treatment operation is: heating to 400-800°C at a heating rate of 2-10°C / min, and keeping the temperature for 1-6h.

9. The nickel disulfide / titanium dioxide / carbon composite material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the nickel disulfide / titanium dioxide / carbon composite material according to claim 9 in preparing anode materials for potassium ion batteries.

Citation Information

Patent Citations

  • Nickel disulfide / double-phase titanium dioxide / carbon nanotube composite material as well as preparation method and application thereof

    CN116137325A

  • Composite material of Co9S8 and titanium dioxide as well as preparation method and application thereof

    CN107326384A

  • Preparation method of multi-level nano-structure lithium-sulfur battery positive electrode material

    CN108242541A

  • Nickel disulfide carbon nano composite material and preparation method and application thereof

    CN108832097A